1977
DOI: 10.1111/j.1600-0560.1977.tb00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Modifications of X‐Irradiated Keratinocytes

Abstract: The number of epithelial cells per unit volume of tissue (NV) and the relative volume (VV) occupied by the spinous and basal layers of X-irradiated and non-irradiated rat-tail epidermis were studied using techniques of stereologic cytology. By a simple calculation, the absolute volumes of basal and spinous keratinocytes were determined in irradiated (and in non-irradiated, control) epidermis, 24, 48, 72 and 96 h after exposure to a single dose of 16 Krads. During this post-irradiation period, the absolute volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, the use of thin (1-2 ,m) sections from plastic-embedded materials has made possible the observation of many morphological details previously not seen by light microscopy, including the dark basal keratinocytes (2,21). In addition, the observation of dark cells by light microscopy allows them to be easily quantitated.…”
mentioning
confidence: 99%
“…However, the use of thin (1-2 ,m) sections from plastic-embedded materials has made possible the observation of many morphological details previously not seen by light microscopy, including the dark basal keratinocytes (2,21). In addition, the observation of dark cells by light microscopy allows them to be easily quantitated.…”
mentioning
confidence: 99%
“…Previous studies in our laboratory have shown the acanthogenic effect of radiation on the rat's tail epidermis Cabrini 1970, de Rey andKlein-Szanto 1972) . This acanthosis, studied as function of the elapsed postirradiation time using high doses of X-radiation, was mainly due to an increased volume of the basal keratinocytes and to a lesser extent to that of the spinous keratinocytes (Klein-Szanto, de Rey and Cabrini 1977) .…”
Section: Introductionmentioning
confidence: 87%
“…Four-day-old Wistar rats were locally irradiated as previously described (KleinSzanto andCabrini 1970, Klein-Szanto et al . 1977) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations